2011
DOI: 10.1177/0095244311404181
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Loading History and Manufacturing Methods on the Mechanical Behavior of High-Density Polyethylene

Abstract: This article describes a series of experiments conducted to determine the effects of loading history and manufacturing techniques on mechanical behavior of high- density polyethylene (HDPE). The main reason for undertaking the research was to investigate multiple creep, multiple relaxation, and cyclic loading on uniaxial tension. The samples used for tensile tests were obtained from extruded pipe and compression-molded sheets. The stress—strain responses of both samples under uniaxial tensile were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…As a result of characterizing the mechanical properties immediately after introducing the loading history, the creep and relaxation behaviour was found to be complicated by the rate-reversal phenomenon, that is, increase and then decrease of stress in the relaxation test and decrease and then increase of strain in the creep test. Such an approach of one test with multiple phases was also used to investigate the effects of loading history and manufacturing techniques on the mechanical behaviour of HDPE [14], from which it was confirmed that the uniaxial tensile behaviour of HDPE shows clear dependence on the manufacturing technique.…”
Section: A N U S C R I P Tmentioning
confidence: 91%
“…As a result of characterizing the mechanical properties immediately after introducing the loading history, the creep and relaxation behaviour was found to be complicated by the rate-reversal phenomenon, that is, increase and then decrease of stress in the relaxation test and decrease and then increase of strain in the creep test. Such an approach of one test with multiple phases was also used to investigate the effects of loading history and manufacturing techniques on the mechanical behaviour of HDPE [14], from which it was confirmed that the uniaxial tensile behaviour of HDPE shows clear dependence on the manufacturing technique.…”
Section: A N U S C R I P Tmentioning
confidence: 91%
“…The most common processing techniques to manufacture HDPE are extrusion, injection molding, blow molding, and compression molding. Manufacturing techniques may influence the mechanical response of HDPE, such as elastic modulus and tensile strength, which could be due to different molecular morphologies and structures in the final product [ 16 ]. It has been shown that the optimization of manufacturing parameters in injection molding results in substantially improved tensile properties [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The third and fourth sets of panels were produced by adding 40 w/% and 50 w/% PE, respectively. 28,29 First, all the panels were prepared of minced composite cardboard and the determined PE amounts; then, the mixtures were placed into a cold mold. After exposure to pressure in the cold mold, the mold was heated to the melting point of PE and the mixture was kept in it for over an hour.…”
Section: Preparation Of Ccpsmentioning
confidence: 99%